Simulation System To Educate People On Phivisp Attack - Salman, Khairul Anuar (2023)
The thesis proposes a simulation system for educating individuals and organisations about PhiViSp attacks, or known as phishing, vishing, and spear phishing. These attacks are a common tactic used by attackers to gain unauthorised access to sensitive information and systems and can be difficult to detect and defend against. The simulation system includes descriptions, examples, scenarios, case studies, interactive exercises, and challenges that allow users to practice identifying and defending against these types of attacks in a safe and controlled environment. Additionally, it provides tips and best practices for recognising and avoiding PhiViSp attacks, including guidance on identifying suspicious emails, websites, and requests for sensitive information. The system is designed to be used by individuals and organisations of all sizes and sectors and will be evaluated through user testing and feedback. It has the potential to significantly reduce the risk of falling victim to these attacks and suffering associated consequences by raising awareness and understanding of these attacks and providing interactive exercises for practicing defense strategies.